The Concept of the ’New Soviet Man’ As a Eugenic Project: Eugenics in Soviet Russia after World War II - Bardziński, Filip (ETHICS IN PROGRESS, 2013)
This article penetrates the idealistic, Marxist concept of the 'new Soviet man', linking it with the notion of eugenics. Departing from a reconstruction of the history and specificity of the eugenic movement in Russia since the late 19th century until the installation of Joseph Stalin as the only ruler of the Soviet Union, Lysenkoism paradigm of Soviet natural sciences is being evoked as a theoretical frame for Soviet-specific eugenic programme. Through referring to a number of chosen – both theoretical (classic Marxist works) and practical (chosen aspects of Soviet science and internal politics) – issues and cases, the concept of the 'new Soviet man' is being confronted with an original reading of eugenics, understood in neo-Lamarckian terms of direct shaping human beings through environmental conditions (comprehending the GULag system of labour camps, pseudo-medical experiments and other) and intergenerational transfer (through inheritance) of acquired traits.